Social and Moral Guidance of Balinese Life in Kakawin Niti Sastra - Ida Bagus Putra Setiawan (Bali Tourism Board, 2023)
Estimated to be written in 350 B.C. In the Magada Kingdom of India, Niti Sastra is one of the knowledge references that gives readers an overview of leadership and management. In Bali, the script is better known as Kakawin Niti Sastra. Kakawin is poetry written in the Kawi language, an extinct old Javanese language. Niti Sastra is the Sanskrit term for